Decision Support System for Provision of Natural Disaster Victim Logistic Assistance with TOPSIS Method - Enok Tuti Alawiah; Sefrika Sefrika (Kresnamedia Publisher, 2020)
At the beginning of 2020, a natural disaster caused many people to lose their homes, damage to public facilities and infrastructure, and the breakdown of transportation links connecting villagers, especially in 3 districts, namely Sukajaya, Nanggung, and Cigudeg. As a result of the disaster, many villages are isolated, and residents need a lot of logistical support to meet their needs. To overcome these problems, we need a system that can help the government and volunteers interested in the decision-making process so that assistance for victims of natural disasters can be right on target and by the urgency of basic needs and logistics needed. Decision support systems using the TOPSIS method are used to solve multicriteria problems by offering various alternative solutions to solve problems. The results obtained a final preference value of 0.68 from C3 criteria to prioritize residents with closed transportation access to channel disaster relief funds for victims of natural disasters in Bogor Regency.